On the mitigation potential of higher urban albedo in a temperate oceanic metropolis. (June 2022) - Falasca, Serena; Zinzi, Michele; Ding, Lan; Curci, Gabriele; Santamouris, Mattheos
Highlights: High resolution modeling of a whole metropolis with 0.5 × 0.5 km 2 grid Detailed urban land use classification based on ten Local Climate Zones 1.4°C maximum of air temperature drop for 0.27 increase of city albedo 260 m maximum of planetary boundary layer height drop for 0.27 increase of city albedo Abstract: The urban overheating calls for the implementation of mitigation actions. The article aims at demonstrating the advantages and the risks associated with the increase of the city albedo in Melbourne (Australia), through high resolution numerical analyses based on a detailed urban land use. The Weather Research and Forecasting model was used to calculate the spatial and temporal local climate change for three increased albedo scenarios and three different urban densities. In the scenario with highest albedo, the ambient temperature decreases of about 1.6°C in the middle and high density zones and 0.9°C in the low density zones. The sea breeze extends the thermal benefit due to the albedo increase to non-urban areas, despite it is slightly weakened by the diminished land-sea temperature contrast. The pollutant levels are expected to increase, due to a combination of slower winds (drops up to 0.19 ms −1 ) and decreased planetary boundary layer heights (drops from 175 m up to 291 m). High and low density classes have the highest and lowest risk of stagnation, respectively. Due to the contrasting results in terms of thermal mitigation and pollution risks, the study calls for the identification of comprehensive metrics to asses optimal values of urban albedo.